2001
DOI: 10.4319/lo.2001.46.3.0730
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of bacterial metabolism in oligotrophic relative to eutrophic waters

Abstract: Heterotrophic bacteria are a key component driving biogeochemical processes in aquatic ecosystems. In 1998, we examined the role of heterotrophic bacteria by quantifying plankton biomass and bacterial and planktonic respiration across a trophic gradient in several small Minnesota lakes as well as Lake Superior. The contribution of bacteria (<1‐ µm fraction) to total planktonic respiration ranged from ~10 to 90%, with the highest contribution occurring in the most oligotrophic waters. The bacterial size fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
241
2
11

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(290 citation statements)
references
References 38 publications
36
241
2
11
Order By: Relevance
“…1) were statistically significant (Table 2). These results are qualitatively similar to those of Biddanda et al (2001) except that, in their study, BR was positively correlated with Chl a concentrations only at low (Ͻ15 g Chl a L Ϫ1 ) concentrations. Their findings suggested that BR attains a maximal rate along a trophic gradient after which it either levels off or decreases (Biddanda et al 2001).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…1) were statistically significant (Table 2). These results are qualitatively similar to those of Biddanda et al (2001) except that, in their study, BR was positively correlated with Chl a concentrations only at low (Ͻ15 g Chl a L Ϫ1 ) concentrations. Their findings suggested that BR attains a maximal rate along a trophic gradient after which it either levels off or decreases (Biddanda et al 2001).…”
Section: Resultssupporting
confidence: 86%
“…The use of larger (1.0 m) nominal cutoff filters in the current study minimizes the extent of this problem. Several other studies (e.g., Cimberlis and Kalff [1998] and Biddanda et al [2001]) have successfully used the Ͻ1.0-m-size fraction to quantify heterotrophic bacteria respiration rates. In fact, Biddanda et al (2001) found that Ͼ95% of heterotrophic bacteria found in unfiltered samples consistently passed through the 1.0-m pore-size filters in their study along a trophic gradient in north temperate lakes similar to those in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned, in stable ecosystems of open ocean and lakes the share of energy consumption by bacteria exceeds 90% (Del Giorgio et al, 1997;Biddanda et al, 2001). The available data on soil bacteria agree with these figures.…”
Section: Energy Consumption Portrait Of the Whole Communitymentioning
confidence: 99%
“…Sprules and Munawar (1986) A similar difference between energy partitioning patterns in stable versus unstable ecosystems can be traced within separate trophic groups. Biddanda et al (2001) measured bacterial respiration in Lake Superior and several small Minnesota lakes, differing greatly in the degree of eutrophy (chlorophyll content from 0.57 to 53 g l −1 ). In the most stable ecosystem of Lake Superior and other oligotrophic lakes bacterial respiration accounts for more than 90% (from 91 to 98%) of the total planktonic respiration.…”
Section: Size Spectra In Aquatic Ecosystemsmentioning
confidence: 99%